Impact of e-WOM and Brand Image on Wardah Product Purchases Among College Students in Surabaya - Febryana, Bella Ayu; Supriyono, Supriyono (International Journal of Economics (IJEC), 2024)
The cosmetics industry in Indonesia is growing rapidly with many local brands competing in the market, including Wardah, which is known as the first halal cosmetic product in Indonesia. The objective of this study is to investigate the influence of electronic word of mouth (eWOM) and brand image on purchasing decisions for Wardah products. A quantitative research method was employed, with a sample size of 100 respondents. Convenience sampling techniques were employed to select the sample for this study. The sample comprised students at Surabaya who had expressed an interest in Wardah products. Partial Least Squares (PLS) was used as the analytical technique, with the data analysed using SmartPLS 4 to conduct validity, reliability and hypothesis testing. The findings of this research demonstrate a positive and statistically significant influence of electronic word of mouth (E-WOM) and brand image upon consumer purchasing decisions in relation to Wardah products.